Exam Night Phenomenon among Students of Babol University of Medical Sciences Iran - Somayeh Mohammadizad; Mehran Aghapour-Joibary (Kerman University of Medical Sciences, 2016)
Background & Objective: The exam night phenomenon is a phenomenon observed among Iranian students in recent years This means that students study the lessons offered during the term only on the night before the exam The aim of this study was to investigate students views and reasons regarding the exam night ‎phenomenon of night Methods: This qualitative study was conducted through phenomenological method and purposive sampling The participants consisted of BSc students of Babol University of Medical Sciences (Iran) who had completed at least two half semesters and had experienced the exam night phenomenon Data were collected through indepth semistructured interviews and analyzed using open coding and a deep coding Results: The 3 main themes of personal problems (mental preoccupation lack of motivation students personality working while studying and study methods) educational issues (teacher textbooks interest in courses and the field of study and compact classes and the resulting fatigue) and implicit issues (university atmosphere family and the influence of friends) were effective in the exam night phenomenon Conclusion: According to the results the exam night phenomenon and its effective factors is an important issue which affects the students study method final score and many other issues